Adsorptive Removal of Cs(I) from Water by Using Persimmon Tannin Impregnated Zeolite - Paudyal, Hari; Pangeni, Bimalal; Inoue, Katsutoshi (Journal of Nepal Chemical Society, 2017)
available with fulltext